The Impact of Covid-19 Pandemic On The Results Of Village-Owned Enterprises (BUMDes) “Bersama Sei Rampah” - Merry Agnes (International Journal of Society and Law, 2023)
The outbreak of covid-19 coronavirus pandemic is now a social reality that must be faced by the world community, especially for the Nation of Indonesia. The fear of covid-19 coronavirus will affect the social attitudes of individual individuals, including villagers. Villages that have the potential of their villages to be managed to improve the welfare of villagers through village-owned enterprises (BUMDes). BUMDes is expected to be the main buffer for national economic growth during the Covid-19 Pandemic. This research is empirical legal research, this research is included in descriptive research. This research tells about the state of BUMDes "Bersama Sei Rampah" in dealing with the obstacles of covid-19 pandemic outbreak in an effort to improve the results of BUMDes. In this study, it can be concluded that in improving the results of BUMDes has not been able to be carried out to the maximum due to the constraints of the covid-19 pandemic that is occurring. The decline in the income of the villagers also influenced the decline in the results of BUMDes "Bersama Sei Rampah".